Uganda : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper analyzes the underlying sources of growth in Uganda, suggesting that the contribution to growth from total factor productivity has been minor, while the high population growth poses a significant challenge to sustain a rapid improvement in living standards. The paper takes a closer look at the monetary transmission mechanisms in Uganda, aimed at assessing the appropriate choice of intermediate target and mix of liquidity sterilization instruments. It also focuses on the recent financial sector reforms undertaken by the government.